Protective effect of neem leaf extract and dexamethasone in cigarette-smoke induced liver and kidney injury in Swiss mice: A comparative analysis - Anushree VERMA; SUBHASHINI; Vishal SRIVASHTAV; Abhinav SINGH (Notulae Scientia Biologicae, 2024)
Cigarette smoke (CS) is one of the leading causes of lung injury where co-morbidity in different organs including liver and kidney can be observed. CS contributes as one of the causes of mortality across the globe. Dexamethasone, a corticosteroid is widely used as an anti-inflammatory medication despite being associated with several side effects with long-term usage. Therefore, the present study focused on the comparison between dexamethasone and Azadirachta indica leaf extract (AILE) for treating hepatic and renal injury caused by CS in mice. The phytochemical screening of AILE revealed the abundance of phytocompounds as sterols, proteins, alkaloids, flavonoids and diterpenes that might have antioxidant and anti-inflammatory activity. In this context, Swiss mice were treated with CS, dexamethasone and AILE. CS-induced mice expressed elevated inflammatory cells, Reactive Oxygen Species (ROS) with higher levels of both liver and kidney function markers: Alanine aminotransferase (ALT), Aspartate aminotransferase (AST) and creatinine respectively which was reversed by AILE. No mortality was observed in CS or AILE-treated group while dexamethasone-treated mice exclusively resulted in 20% mortality. Moreover, CS-induced mice also exhibited declined SOD levels in the liver and kidney and higher Eosinophil peroxidase (EPO) which was modulated by AILE treatment. This is the first report demonstrating in vivo the effects of A. indica ethanolic leaf extract in treating CS-induced hepatic and renal chronic inflammation in an animal model which gave better results when compared to dexamethasone.